2020
DOI: 10.1111/1471-0307.12731
|View full text |Cite
|
Sign up to set email alerts
|

Role of soy lecithin on emulsion stability of dairy beverages treated by ultrasound

Abstract: Role of soy lecithin on emulsion stability of dairy beverages treated by ultrasound.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…This phenomenon was attributed to the turbulence and high shear induced by the cavitation phenomenon of HIU treatment as the ultrasound power increased, which broken down most of the droplets and made the distribution of droplets more uniform [ 27 ]. Nyuydze et al [ 28 ] revealed that the particle size of the emulsion could be effectively minimized with increasing ultrasound intensity. Whereas, the particle size of emulsion at 450 W (2.91 ± 0.39 μm) and 600 W (3.33 ± 0.51 μm) gradually became larger.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon was attributed to the turbulence and high shear induced by the cavitation phenomenon of HIU treatment as the ultrasound power increased, which broken down most of the droplets and made the distribution of droplets more uniform [ 27 ]. Nyuydze et al [ 28 ] revealed that the particle size of the emulsion could be effectively minimized with increasing ultrasound intensity. Whereas, the particle size of emulsion at 450 W (2.91 ± 0.39 μm) and 600 W (3.33 ± 0.51 μm) gradually became larger.…”
Section: Resultsmentioning
confidence: 99%
“…A smaller protein aggregate size and a higher concentration are beneficial to preparing smaller oil droplet sizes. Also, an increased surface hydrophobicity would result in proteins having a greater surface activity (Nyuydze & Martínez-Monteagudo, 2020). However, after two weeks storage, the first peak intensity decreased while the second one increased, indicating that the average D 4,3 and D 3,2 appeared to change significantly.…”
Section: Zeta Potentialmentioning
confidence: 97%
“…O'Sullivan et al [48] also found no differential effect of ultrasonic on the protein content of milk protein isolate and whey protein isolate. Applications of ultrasound in test sound intensity range did not have obvious effects on the primary structure of the protein, which might be related to ultrasound-induced changes in protein structure that might be caused by hydrophobic interactions (non-covalent) rather than peptide cleavage [49] . In addition, the main protein in the MFGM was cluster of differentiation 36 (CD36), butyrophilin (BTN), adipophilin (ADPH), and periodic acid Schiff glycoprotein 6/7 (PAS6/7), with molecular weights of 77 kDa, 67 kDa, 52 kDa, and 48 kDa, respectively.…”
Section: Resultsmentioning
confidence: 94%